Analysis On The Financial Performance And Operational Efficiency Of Companies Listed On The Indo-nesia Stock Exchange Before And After Acquisition For The 2019-2022 Period - Nurul Rahmah (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to examine the differences in financial performance and operational efficiency before and after acquisitions in companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The sample was selected purposively, focusing on publicly listed non-financial companies. The data used in this study are secondary data obtained from audited financial statements or annual reports. The sample consists of companies that conducted acquisitions, with observations made both before and after the acquisition year. This study uses the non-parametric Wilcoxon Signed-Rank Test for analysis. The results of this study indicate that there are no significant differences in the financial performance and operational efficiency of parent companies before and after acquisitions, as measured by economic value added, return on assets, return on equity, net profit margin, and efficiency ratio.